Improve Community-Based Tourism to Bolster Feasible Tourism in Setu Babakan Jagakarsa South Jakarta - H Demolingo, Ramang; Pradini, Gagih; Efendi, Suryono; Ari Wibowo, Toni (Jurnal Toursci, 2024)
Community-based tourism (CBT) is advancing through community strengthening in arranging and administration. This investigation points to applying the CBT demonstration to the Setu Babakan range and realizing maintainable tourism improvement. Openness and offices not legitimately overseen by the neighborhood community and the need for back from the nearby government make the Setu Babakan area's social legacy not broadly known to visitors. In any case, the number of traveler visits started to increase. This investigation makes the Setu Babakan zone one of the tourism options for visitors going by DKI Jakarta. The inquiry about the approach is subjective and clear through the investigation of qualities, shortcomings, Opportunities, and Threats (SWOT), which can outline the qualities, shortcomings, openings, and deterrents within the Setu Babakan region. Investigating information is essential information sourced from interviews, surveys, and perceptions. It appears that the individuals of the Setu Babakan region concur with the usage of CBT. The improvement of Smaller, small, and Medium enterprises is still not ideally carried out, so the part of government is required to bolster and encourage (MSMEs). The Setu Babakan traveler zone is an extraordinary financial zone (SEZ) that can emphatically affect the community's welfare.